Pemantauan Tumbuh Kembang Anak sebagai Upaya Pencegahan Stunting di Posyandu Bengkong Abadi Baru Kota Batam - Roza Erda; Isna Aglusi Badri; Nurma Zela Gustina; Yulia Devi Putri; Resi Novia; Nahrul Hayat (Lembaga Pengembangan Kinerja Dosen, 2025)
Monitoring child growth and development can be one of the efforts in preventing stunting. The role of mothers is very important in monitoring child growth and development so that providing education to mothers about monitoring child growth and development can be an effort to prevent stunting in the future. This activity was carried out at the Bengkong Abadi Baru Posyantu in Batam City using lecture and direct practice methods. The material presented included child growth and development, and the use of child growth and development monitoring media. The results of the activity showed that participants had a high interest in understanding how to monitor child growth and development according to their age. In addition, the role of cadres in providing further guidance encouraged an increase in participants' willingness to participate in the program. This activity shows that providing education that is in accordance with the abilities of participants and involving cadres can be an effort to prevent stunting. The success of this program in the long term requires ongoing support from health workers to make this education program a routine activity in every posyandu. Through this activity, it is hoped that a community attitude can be created that is aware of the importance of monitoring growth and development to prevent stunting.